The Malaysian 14th General election: media use and trust among party supporters - Syed Abdullah Idid, Syed Arabi (2018)
This paper discusses the use and role of media among voters during elections. Electronic and print media, and other communication sources play a vital role in disseminating information about politics, public affairs and current events. Information increases a person’s interest and knowledge of politics, and provides him substance to hold his opinion on issues. The information obtained from the traditional and the new media or from interpersonal sources, enable voters to make reasoned decision when casting their votes during elections. Media channels have transformed the way members in society think and discuss about news. One associates media’s responsibility and accountability for providing citizens with political and social information as part of their role in developing democracy (Vraga et al. 2012).